2005
DOI: 10.1111/j.1742-4658.2005.04689.x
|View full text |Cite
|
Sign up to set email alerts
|

The binding of foot‐and‐mouth disease virus leader proteinase to eIF4GI involves conserved ionic interactions

Abstract: The leader proteinase (Lpro) of foot‐and‐mouth disease virus (FMDV) initially cleaves itself from the polyprotein. Subsequently, Lpro cleaves the host proteins eukaryotic initiation factor (eIF) 4GI and 4GII. This prevents protein synthesis from capped cellular mRNAs; the viral RNA is still translated, initiating from an internal ribosome entry site. Lpro cleaves eIF4GI between residues G674 and R675. We showed previously, however, that Lpro binds to residues 640–669 of eIF4GI. Binding was substantially improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Meanwhile, residue Leu143 also determines the cleavage specificity of Lb pro [104]. Lb pro has a flexible C-terminal extension (CTE) of residues Asp184-Lys201, which are involved in self-processing and recognition of eIF4G [54,60]. The crystal structure of CTE in full-length Lb pro reveals that Lb pro appears to be a dimer because of the CTE folding back and interacting with the active site of a neighboring molecule, whereas that of sLb pro lacking six C-terminal amino acid residues is undefined because it cannot be traced in the electron density ( Fig.…”
Section: Non-structural Proteinsmentioning
confidence: 99%
“…Meanwhile, residue Leu143 also determines the cleavage specificity of Lb pro [104]. Lb pro has a flexible C-terminal extension (CTE) of residues Asp184-Lys201, which are involved in self-processing and recognition of eIF4G [54,60]. The crystal structure of CTE in full-length Lb pro reveals that Lb pro appears to be a dimer because of the CTE folding back and interacting with the active site of a neighboring molecule, whereas that of sLb pro lacking six C-terminal amino acid residues is undefined because it cannot be traced in the electron density ( Fig.…”
Section: Non-structural Proteinsmentioning
confidence: 99%
“…Both possess similar biochemical activities and are functionally interchangeable (39). The FMDV L protease cleaves both eIF4GI and eIF4GII (13,15,46), inactivating the eIF4F complex in terms of its ability to recognize capped mRNAs, which results in a reduction of cap-dependent translation initiation (15,39). Interestingly, the carboxy-terminal fragment of eIF4G generated by FMDV L protease cleavage efficiently supports and indeed stimulates cap-independent translation initiation (9, 33).…”
Section: Vol 84 2010mentioning
confidence: 99%
“…We have shown that Lb pro can contact the eIF4G homologues using a site away from the canonical substrate-binding cleft. 14,15 Nevertheless, the dimer still has to come apart so that the eIF4G substrate can enter the active site of Lb pro to allow proteolytic cleavage.…”
Section: Investigating Lb Pro Substrate Binding Using Oligopeptidesmentioning
confidence: 99%
“…The CTE has been shown, together with Cys133, to have a role in recognising eIF4G, even though it is some 30 Å distant from the active site. 5,14,15 The CTE is clearly defined in the crystal structure of full-length Lb pro (PDB ID code 1QOL). The CTE of one molecule lies in the active site of an adjacent molecule and vice versa, 12 so that Lb pro appears as a dimer.…”
Section: Introductionmentioning
confidence: 99%